Exploring Emotional Speech Acts in It ends with us: A Pragmatic Study of Relational Dialogues - Maisaroh, Ajeng Dilla; Meisuri, Meisuri; Jenica, Martha; Aulia, Delvi (International Journal of English and Applied Linguistics (IJEAL), 2024)
This study investigates the use of emotional speech acts in Colleen Hoover's It Ends with Us, focusing on how characters navigate relational conflicts using expressive and commissive speech acts. Using a pragmatic framework based on Searle's speech act theory and Baxter and Montgomery's Relational Dialectics Theory, the research examines chapters 23-35 of the novel, which are rich in emotional and relational dialogue. A qualitative method of dialogue transcription and coding reveals 144 speech acts, with expressive acts accounting for 76% and reflecting emotions such as guilt, love, and regret. Commissive acts, which account for 24%, emphasize promises and commitments that influence relational dynamics. The findings emphasize the significance of language in expressing emotions and resolving interpersonal conflicts. Expressive acts frequently reveal characters' vulnerabilities, whereas commissive acts emphasize their intentions to mend relationships or make future commitments. This interaction demonstrates the complexities of emotional communication, particularly in the context of trauma and recovery. This study adds to pragmatic research by demonstrating how emotional speech acts shape interpersonal dynamics in literary texts, revealing how language mirrors real-life emotional communication. By focusing on It Ends with Us, this study bridges the gap between literary analysis and linguistic pragmatics, providing a more nuanced understanding of how emotional and relational tensions are managed through language. The findings emphasize language's transformative power in navigating love, betrayal, and resilience, which is consistent with broader discussions about emotional communication in various contexts.